Performance Evaluation and Comparison of GRP and OLSR Routing Protocols for Video Streaming Over Mobile Ad Hoc Networks Using OPNET 14.5: مقارنة وتقييم الأداء لبروتوكولات التوجيه (GRP، OLSR) في إرسال الفيديو عبر الشبكات الخاصة المتنقلة باستخدام OPNET 14.5 - Hanadi Yahya Darwisho (Journal of engineering sciences and information technology, 2019)
Due to the increased use of mobile devices with the high demand for applications such as video application, most companies have tended to pay attention to Mobile Ad hoc Networks. This type of network is characterized by multi-hop wireless networks where data packets are sent in a "store and forward" manner from the source to an arbitrary destination via intermediate nodes. The mobile nodes are connected by multi-routes routing as the nodes in this network not only serve as hosts but also as routers where data is routed to and from other nodes in the network and therefore the mobile node not only sends its data packets but also sends data packets of other mobile nodes. The network architecture changes dynamically, mainly because of Mobility of nodes, so we need routing protocols to establish the connection. Routing protocols are categorized into proactive routing protocols, reactive routing protocols and hybrid routing protocols. So in this research, we has been studied Geographical Routing Protocol (GRP ), Optimized Link State Routing Protocol (OLSR) routing protocols which is one of proactive routing protocols and hybrid routing protocols respectively on the basis of Throughput, Delay and Load..etc and evaluated the performance in a large mobile ad hoc network and in a small mobile ad hoc network as well as for different video resolutions, the OPNET 14.5 network simulator was used to obtain research results. It was found that the GRP protocol performs better for a small number of nodes whether the video resolution is low or high while its performance decreases when the number of nodes increases in the network but the OLSR protocol improves when the number of nodes is increased.